Effect of burner head geometry on flame dispersion in gas stoves with hydrogen and natural gas blends - Sorgulu, Fatih; Ozturk, Merve; Javani, Nader; Dincer, Ibrahim (ELSEVIER, 2024)
The main goal of the current study is to investigate how the gas stove burner geometry affects flame behavior and, consequently, combustion performance. To fulfill this objective, both natural gas and hydrogen-natural gas blends are experimentally investigated to assess their burning performance. Among the different geometries, six burner geometries are designed and manufactured for experimental studies. For each of the considered six burner heads, an identical volumetric flow rate of 5 liters per minute is used to evaluate the pure natural gas and the hydrogen-natural gas blend (by 30% volumetric hydrogen) to analyse how the geometry affects the flame distribution and burning quality. In different time steps of 1, 5, and 10 s, the flame picture is captured to compare its variations and combustion behavior. The experiments are repeated for every geometry to guarantee steady circumstances and produce accurate images. The experimental results show that by injection of the hydrogen, the height of the flame shortens while the flame color tends to be bluish, implying better combustion. This is more pronounced in the geometry with three lateral sets of holes and two circular sets of holes at the top of the burner. Furthermore, the present results show that the width to height ratio of the flame changes between 0.27 and 0.67.
Keywords: Natural Gas; Hydrogen; Hydrogen blend; Combustion; Burner head; Flame; EMISSIONS; Engineering